Network Security to Protect Negative Web: A Case Study of the Government of Aceh - Syafrinal Syafrinal; Abdus Salam (Jurnal Mantik, 2021)
The specific objectives of the research include evaluating the extent to which information governance management has been carried out at the Aceh Communications, Information and Encryption Service, and negative web protection that is accessed through the aceh government network in all OPDs and districts/cities throughout Aceh. This research will use 4 (four) stages of information system security audit including; audit planning, preparation, implementation, and reporting. Information system security audit. There are several conclusions drawn based on the discussion on the results of the analysis. The conclusions drawn from this study are 1) Based on the results obtained from this practical work course project, almost all HTTP and HTTPS protocol websites can be blocked using the filtering techniques available on MikroTik, 2) Using a VPN is almost impossible to block using MikroTik because the settings proxy to block VPN is very complicated, and 3) Mikrotik device is able to block almost all websites using Layer7 and mangle and can't turn off VPN traffic.